The Sonoran Desert : a literary field guide - Cokinos, Christopher; Magrane, Eric (The University of Arizona Press, 2016)
"This is an anthology of poetry and short prose about the Sonoran Desert that is organized in the manner of a field guide"--Provided by publisher.